The Evolutionary History of Common Genetic Variants Influencing Human Cortical Surface Area. (9th December 2020) - Tilot, Amanda K; Khramtsova, Ekaterina A; Liang, Dan; Grasby, Katrina L; Jahanshad, Neda; Painter, Jodie; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P; Lind, Penelope A; Liu, Siyao; Brotman, Sarah M; et al.
Abstract: Structural brain changes along the lineage leading to modern Homo sapiens contributed to our distinctive cognitive and social abilities. However, the evolutionarily relevant molecular variants impacting key aspects of neuroanatomy are largely unknown. Here, we integrate evolutionary annotations of the genome at diverse timescales with common variant associations from large-scale neuroimaging genetic screens. We find that alleles with evidence of recent positive polygenic selection over the past 2000–3000 years are associated with increased surface area (SA) of the entire cortex, as well as specific regions, including those involved in spoken language and visual processing. Therefore, polygenic selective pressures impact the structure of specific cortical areas even over relatively recent timescales. Moreover, common sequence variation within human gained enhancers active in the prenatal cortex is associated with postnatal global SA. We show that such variation modulates the function of a regulatory element of the developmentally relevant transcription factor HEY2 in human neural progenitor cells and is associated with structural changes in the inferior frontal cortex. These results indicate that non-coding genomic regions active during prenatal cortical development are involved in the evolution of human brain structure and identify novel regulatory elements and genes impacting modern human brain structure.